Overt and covert institutionalization in Europe - Adrienne Héritier (Max-Planck-Projektgruppe Recht der Gemeinschaftsgüter, 2000)
Observers of the European policy-making process are inevitably struck by the contrast between cumbersome decision-making processes on the one hand and simultaneous swift policy developments on the other. Many policies seem to be stuck for long periods in the Council, while at the same time similar measures are introduced under a different guise along a different path. A case in point is European anti-poverty policy. At the very time when this measure was bogged down in a Council deadlock, it was reintroduced by the Commission, couched in different terms in a new political context. In the end it was elevated to official status in the Amsterdam Treaty. A further example of a similar process was in European telecommunications policy which initially met with strong resistance from member states. As a result of the Commission's skilful use of all kinds of soft measures, such as offering research funds to industry and actively creating a supportive policy network, it finally became established as a regular European policy. Or, to cite an example from general procedure: the main avenue of European policy-making in the Council often stalls because of the need for consensus, whereas Court rulings and Commission decisions are not hindered by this requirement. Consequently, the emphasis of European policy expansion has often shifted to the European Court of Justice's and the Commission's legal interpretation of rules which exist under the Treaty of Rome. This has given European policies a bias in favour of free trade and free competition. At the same time market-correcting measures and the pursuit of distributive goals remain entangled in the gridlock of Council decision-making processes and are pushed into the background...
Keywords: 330; EU-Politik; Institutioneller Wandel; Neue politische Ökonomie; EU-Staaten